Loss of endogenous Nox2-NADPH oxidase does not prevent age-induced platelet activation and arterial thrombosis in mice - Azaj Ahmed; Gokul Patil; Vijay K. Sonkar; Melissa Jensen; Jennifer Streeter; Sanjana Dayal (Research and Practice in Thrombosis and Haemostasis)
Background: Reactive oxygen species are known to contribute to platelet hyperactivation and thrombosis during aging; however, the mechanistic contribution of the specific oxidative pathway remains elusive. Objectives: We hypothesized that during aging, endogenous Nox2-NADPH oxidase contributes to platelet reactive oxygen species accumulation and that loss of Nox2 will protect from platelet activation and thrombosis. Methods: We studied littermates of Nox2 knockout (Nox2-KO) and -wild-type (Nox2-WT) mice at young (3-4 months) and old (18-20 months) age. Within platelets, we examined the expression of subunits of NADPH oxidase and enzyme activity, oxidant levels, activation markers, aggregation, and secretion. We also assessed susceptibility to in vivo thrombosis in 2 experimental models. Results: While aged Nox2-WT mice displayed increased mRNA levels for Nox2, aged Nox2-KO mice showed an increase in Nox4 mRNA. However, neither the protein levels of several subunits nor the activity of NADPH oxidase were found to be altered by age or genotype. Both aged Nox2-WT and aged Nox2-KO mice exhibited similar enhancement in levels of platelet oxidants, granule release, αIIbβ3 activation, annexin V binding, aggregation and secretion, and a greater susceptibility to platelet-induced pulmonary thrombosis compared with young mice. In a photochemical injury model, adoptive transfer of platelets from aged Nox2-WT or Nox2-KO mice to the aged host mice resulted in a similar time to develop occlusive thrombus in the carotid artery. These findings suggest that loss of endogenous Nox2 does not protect against age-related platelet activation and arterial thrombosis in mice. Conclusion: We conclude that Nox2 is not an essential mediator of prothrombotic effects associated with aging.